Dunite in Agriculture: Physiological Changes, Nutritional Status and Soybean Yield - Moretti, L. G. [UNESP]; Bossolani, J. W. [UNESP]; Crusciol, C. A.C. [UNESP]; Moreira, A.; Micheri, P. H. [UNESP]; Rossi, R. [UNESP]; Imaizumi, C. [UNESP] (Taylor & Francis, 2019)
Brazil is an importer of fertilizers and the use of alternative sources is increasing in agriculture. The objective of this study was to evaluate the effect of Dunite rates on magnesium (Mg), silicium (Si), reducing sugars, sucrose and foliar starch, soil chemical attributes and soybean yield [Glycine max (L.) Merril] in two soil types. The treatments consisted in the five Dunite rates (0, 42, 208, 542, and 1542 mg kg−1) in a clayey soil, and five Dunite rates (0, 150, 238, 411, and 933 mg kg−1) in a sandy soil. In both crops and soils, the Mg and Si contents, reducing sugars and foliar glucose, as well as pH, Mg and Si of the soil, and yield components showed a positive response due to the increase of input rates. The Mg nutrition provides lower foliar starch levels, consequently, the best partition of metabolites to plant leads to better development, filling and yield of soybeans.
Keywords: Glycine max; magnesium fertilization; metabolites; silicium